2007
DOI: 10.1097/brs.0b013e31815a5943
|View full text |Cite
|
Sign up to set email alerts
|

Association Between IL-6 and MMP-3 Gene Polymorphisms and Adolescent Idiopathic Scoliosis

Abstract: This is the first study that has evaluated the possibility that gene variants of IL-6 and MMPs might be associated with scoliosis and suggests that MMP-3 and IL-6 promoter polymorphisms constitute important factors for the genetic predisposition to scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 15 publications
(10 reference statements)
3
30
0
1
Order By: Relevance
“…The combined sympathetic-hormonally-induced effects in the lower BMI subset produce mean Cobb angle and mean upper arm length asymmetry similar to, and mean AVR less than, the higher BMI subset (Figure 6) [46]. This postulate of an inverse relationship ignores other possible mechanisms that may contribute to curve progression common to each BMI subset, including osteopenia [88,278,279], biomechanical spinal growth modulation [80-82], intervertebral disc degeneration [45,342-351], and platelet calmodulin dysfunction [21,22,107]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined sympathetic-hormonally-induced effects in the lower BMI subset produce mean Cobb angle and mean upper arm length asymmetry similar to, and mean AVR less than, the higher BMI subset (Figure 6) [46]. This postulate of an inverse relationship ignores other possible mechanisms that may contribute to curve progression common to each BMI subset, including osteopenia [88,278,279], biomechanical spinal growth modulation [80-82], intervertebral disc degeneration [45,342-351], and platelet calmodulin dysfunction [21,22,107]. …”
Section: Discussionmentioning
confidence: 99%
“…These are explained by the interaction of autonomic and somatic nervous systems in the spine and trunk compounded by any relative osteopenia of vertebrae [88,278,279], biomechanical spinal growth modulation [80-82], accelerated disc degeneration [45,342-351], and platelet calmodulin dysfunction [21,22,107]. Circulating leptin levels in AIS girls did not correlate significantly with Cobb angle [163,164].…”
Section: Discussionmentioning
confidence: 99%
“…These all supported that CALM1 gene was likely to be a susceptibility gene associated with the etiology of AIS. Compared to the genetic susceptible factors, SNP sites would not produce an effect on the occurrence and development of diseases independently, they functioned together and intrinsically correlated with each other, haplotype was a reflection of genetic linkage, and, therefore, study of the haplotype could reveal the association between multiple SNPs loci and disease susceptibility [1315]. Based on the haplotype analysis of the SNPs, frequencies were higher than 10%, and its haplotype distributions were different between case group and control group, and we got 1 positive haplotype: SNP8C-SNP01A-SNPl3C-SNPl4C-SNP02C-SNP3T-SNP4G-SNP05T-SNP011C; this again showed that CALM1 gene was possible to be a susceptibility gene of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis mainly affects girls in number and severity; several familial surveys of idiopathic scoliosis provided strong evidence that genetic factors have a role in this condition [7]. Single nucleotide polymorphisms (SNPs) in the genes for estrogen receptor a (ESR1) [8], estrogen receptor b (ESR2) [9], matrilin 1 (MATN1) [10], melatonin receptor 1B (MTNR1B) [11], tryptophan hydroxylase 1 (TPH1) [12], interleukin-6 (IL-6), and matrix metalloproteinase-3 (MMP-3) [13] have been reported to be associated with AIS predisposition. However, many scientists believe that there are still some more candidate genes that need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…(MMP-2 and MMP-9) seem to be decreased after exposure of disc cells to mechanical forces [35]. Regarding the role of MMPs family in idiopathic scoliosis, there are some contradictory findings in the literature about the role of gene variants of IL-6 and MMP-3 and whether MMP-3 and IL-6 promoter polymorphisms constitute important factors for the genetic predisposition to idiopathic scoliosis [36,37]. …”
Section: Discussionmentioning
confidence: 99%